Hubungan Peran Perawat Sebagai Edukator dan Dukungan Keluarga dengan Self-care Management pada Penderita Hipertensi - Shinta Amelia Oktaviani; Retno Setyawati; Suyanto Suyanto (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Hypertension is a non-communicable disease that is often referred to as "the silent killer" because of its asymptomatic nature. Surgical education plays an important role in providing important information and motivational support to hypertensive patients, which has the potential to increase the effectiveness of treatment. In addition, family involvement is the main foundation for successful monitoring and prevention of complications, because hypertension management is highly dependent on effective self-care management. This study used a quantitative descriptive correlational research design with a cross-sectional approach. Data collection used a questionnaire given to 75 participants registered in the Hypertension Chronic Disease Management Program in the Bangetayu and Tlogosari Kulon Health Centers. Statistical analysis used the Somer'd correlation test. Among the 75 study respondents, 92% (n = 69) rated the role of nurses as good educators, while 88% (n = 66) reported good family support, and 84% (n = 63) showed good self-care management. Statistical analysis revealed a significant correlation between the role of nurses as educators with self-care management of hypertension patients (p=0.016, correlation coefficient=0.525). Likewise, family support showed a significant relationship with self-care management (p=0.01, correlation coefficient=0.491). This study shows that there is a significant relationship between the role of nurses as educators and family support with self-care management in hypertension patients in the working areas of Bangetayu Health Center and Tlogosari Kulon Health Center.